Korelasi Jumlah Repositori Karya Akhir pada Repositori Perpustakaan dan Jumlah Artikel di Scopus tentang Perpustakaan - Prasetyo Adi (Perpustakaan Nasional, 2022)
Indonesia has a lower number of research quality than other countries. Repositories of scientific works through university libraries in Indonesia can be an alternative reference for academics in compiling research. Academic writings published by academics of a campus can be a reference for other academics to compile further research. This study aims to analyze whether there is a correlation between the number of scientific papers and publications on Scopus. This study uses quantitative methods with secondary data. The independent variable is the number of scientific works majoring in information science libraries at the Airlangga University library. The dependent variable is the number of publications on the Scopus website. Data were analyzed by simple linear regression method. The data range of this study is for the last five years, namely from 2014 to 2021. The results of this study indicate that the F value is proven to be significant because the P-Value is below 0.05. This proves that the number of theses significantly affects the number of publications on Scopus with topics or majors about libraries. This is because in addition to the campus requires a lot of research outputs, namely publications, there are also many theses that can be developed so that they can be used as good writings, so that they can be published in Scopus indexed journals. Based on the results of the study, it can be concluded that the largest number of theses was produced in 2017, but did not correlate with the number of papers on Scopus in 2017.